Characteristics and drainage modes of coalbed methane resources in closed coal mines in Yangquan and Jincheng Mining Areas - Yang WANG; Jie XIANG; Yong QIN; Shangbin CHEN; Yanming ZHU; Manli HUANG; Ying SHI (Meitan kexue jishu)
Affected by factors such as coal resources exhaustion, elimination of outdated and excess capacity, the number of closed coal mines in Shanxi Province has increased year by year, and the evaluation and exploration of closed or abandoned coal mine coalbed methane resources has gradually received attention. In this study, the closed coal mines in Yangquan and Jincheng Mining Areasare taken as the research object. Through data collation, experimental test, numerical simulation and other means, the characteristics of coalbed methane resources in closed coal mines are explored, the amount of coalbed methane resources is predicted, and the drainage modesare summarized. The research shows that 153 coal mines in Yangquan and Jincheng Mining Areas were closed before and during the merger and reorganization in 2009, whose were dominated by low-gas coal mine. From 2016 to 2020, 37 coal mines were closed due to capacity elimination. The closed coal mines in Yangquan Mining Area are concentrated and mainly high-gas mines. The distribution of closed coal mines in Jincheng Mining Area is relatively scattered with mainly low-gas mines. The coalbed methane resources in closed coal mine are composed of gob coalbed methane resources and in-situ coalbed methane resources. Gob coalbed methane mainly exists in the pore-fracture of gob as the free state. The ratio I of the sum of pore-fracture volume in the caving zone and fracture zone of gob to the working face volume in thick coal seam ranges from 0.53 to 0.73, while that in medium-thick coal seam is generally greater than 0.90. The in-situ coalbed methane is mainly adsorbed in the pores of coal matrix. The porosity of No.15 coal seam is between 3.69%～5.45%, the specific surface area of micropores is 97.58～120.76 m2/g, and the volume of micropores ranges from 0.017～0.022 cm3/g, indicating that micropores are the most developed. The depth of coal seam and the local geological structure control the gas content of the in-situ coal seam, while as an important index of the gas content of the gob, methane concentration is controlled by the coal seam, gas storage space structure and sealing conditions. According to the characteristics of resources and closed coal mines, the closed coal mine coalbed methane resources are divided into three categories: gob coalbed methane resources in low-gas closed coal mine, gob coalbed methane resources in high-gas closed coal mine, and in-situ coalbed methane resources in high-gas closed coal mine.The amount of gob coalbed methane resources in closed coal mines was predicted by constructing a new mathematical model. Besides, the amount of the in-situ coalbed methane resourceswas predicted by the volume method. Within the range of resourceprediction, the total amount of gob coalbed methane resources is 46074.01×104 m3, and the amount of in-situ coalbed methane resources can reach 146388.12×104 m3, among which Yangquan No.3 Mine has the largest amount. In addition, four coalbed methane drainage modes in closed coal mines are summarized, including surface vertical well drainage, L-shaped well drainage, co-drainage of gob and horizontal adjacent in-situ coalbed methane resources, and coalbed methane drainage under gob. Furthermore, the utilization direction is proposed for each closed coal mine.